Inside Cover: Regioselective Synthesis of Polyheterohalogenated Naphthalenes via the Benzannulation of Haloalkynes (Chem. Eur. J. 50/2015). Issue 50 (7th December 2015) - Lehnherr, Dan; Alzola, Joaquin M.; Lobkovsky, Emil B.; Dichtel, William R.
Abstract : Polyheterohalogenated naphthalenes are synthesized by using a copper‐catalyzed regioselective benzannulation of chloro‐, bromo‐, and iodoalkynes. This modular approach based on readily available haloalkynes and benzaldehydes provides independent control of halide substitution at six of the seven naphthalene positions of 2‐arylnaphthalenes. Insight into the reaction mechanism and the origin of the regioselectivity is described by W. R. Dichtel et al. in their Full Paper onpage 18122 ff.